a)
[tex](3a + 4b) – (2a – 5b) – (3a – 2b)= \\ = 3a + 4b –2a + 5b – 3a + 2b= \\ = 3a - 2a - 3a + 4b + 5b + 2b = \\ = - 2a + 11b[/tex]
b)
[tex] (6x – 8y + 12) – ( -3x +2y + 7)= \\ = 6x – 8y + 12 + 3x - 2y - 7= \\ = 6x + 3x - 8y - 2y + 12 - 7 = \\ = 9x - 10y + 5[/tex]
c)
[tex]–4(2y – 1) + 6(y – 2)= \\ = –8y + 4 + 6y – 12= - 2y - 8[/tex]
d)
[tex](12a – 16b):4 + (9a – 15b): (-3)= \\ = \frac{12a - 16b}{4} + \frac{9a - 15b}{ - 3} = \\ = \frac{4(3a - 4b)}{4} + \frac{ - 3( - 3a + 5b)}{ - 3} = \\ = 3a - 4b + ( - 3a + 5b) = \\ = 3a - 3a - 4b + 5b = \\ = b[/tex]
e)
[tex](20x + 25y):5 + (14x – 21y):7= \\ = \frac{20x + 25y}{5} + \frac{14x - 21y}{7} = \\ = \frac{5(4x + 5y)}{5} + \frac{7(2x - 3y)}{7} = \\ = 4x + 5y + 2x - 3y = \\ = 6x + 2y[/tex]